2020
DOI: 10.3390/s20215970
|View full text |Cite
|
Sign up to set email alerts
|

An API for Wearable Environments Development and Its Application to mHealth Field †

Abstract: Wearable technologies are transforming research in traditional paradigms of software and knowledge engineering. Among them, expert systems have the opportunity to deal with knowledge bases dynamically varying according to real-time data collected by position sensors, movement sensors, etc. However, it is necessary to design and implement opportune architectural solutions to avoid expert systems are responsible for data acquisition and representation. These solutions should be able to collect and store data acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…There have been some efforts to develop integration APIs or mobile and web applications for handling the issues above. After careful review, we have identified three domain-related categories: medical applications [4,5,1,6], social and psychological applications [7,8] and data analysis applications [9,2]. However, the majority of these works do not use mobile health data interoperability standards for standardizing and harmonizing data from disparate sources, nor have they made their code open-source, while others support only a limited amount of manufacturers [4].…”
Section: Introductionmentioning
confidence: 99%
“…There have been some efforts to develop integration APIs or mobile and web applications for handling the issues above. After careful review, we have identified three domain-related categories: medical applications [4,5,1,6], social and psychological applications [7,8] and data analysis applications [9,2]. However, the majority of these works do not use mobile health data interoperability standards for standardizing and harmonizing data from disparate sources, nor have they made their code open-source, while others support only a limited amount of manufacturers [4].…”
Section: Introductionmentioning
confidence: 99%